Assessment of Natural Lighting at the Interior Part of G3 Classroom - NORRAIN, WAN MUHAMAD FAIZ BIN; Ismail, Lokman Hakim (Recent Trends in Civil Engineering and Built Environment, 2021)
Classroom is a place where every student use in their daily life for various purpose related to education. Being the most used room it is important for the room to provide good visual comfort for the educators and students. There were a lot of classes are used in a day especially in university nowadays. Most of the are using artificial light as their main source of room lighting. A huge number of classroom will used up tremendous energy to provide the best illumination for reading and writing usage. Therefore to reduce the waste of energy, it is brilliant to utilize the natural lighting to illuminate the interior part of the building. This study was carried out to assess the natural lighting in the classroom of G3 in UTHM as sample for any other classes. The level of natural lighting is assess and compared to standard requirement guideline provided OSH. Based on the finding conducted at 10 classrooms around the G3 building at 4 different time the highest illumination recorded was168 lux which is no where near the standard illumination required which 500 lux. From this we have learn that G3 classroom need artificial lighting to illuminate the interior part of the building. In order to utilize the natural lighting in G3 building some modification is required to gain the efficient natural light.